Metagenomic Profile of the Viral Communities in Rhipicephalus spp. Ticks from Yunnan, China - Xia, Han; Hu, Cheng; Zhang, Dake; Tang, Shuang; Zhang, Zhong; Kou, Zheng; Fan, Zhaojun; Bente, Dennis; Zeng, Changqing; Li, Tianxian (PloS one, 2015)
Besides mosquitoes, ticks are regarded as the primary source of vector-borne infectious diseases. Indeed, a wide variety of severe infectious human diseases, including those involving viruses, are transmitted by ticks in many parts of the world. To date, there are no published reports on the use of next-generation sequencing for studying viral diversity in ticks or discovering new viruses in these arthropods from China. Here, Ion-torrent sequencing was used to investigate the presence of viruses in three Rhipicephalus spp. tick pools (NY-11, NY-13, and MM-13) collected from the Menglian district of Yunnan, China. The sequencing run resulted in 3,641,088, 3,106,733, and 3,871,851 reads in each tick pool after trimming. Reads and assembled contiguous sequences (contigs) were subject to basic local alignment search tool analysis against the GenBank database. Large numbers of reads and contigs related to known viral sequences corresponding to a broad range of viral families were identified. Some of the sequences originated from viruses that have not been described previously in ticks. Our findings will facilitate better understanding of the tick virome, and add to our current knowledge of disease-causing viruses in ticks living under natural conditions.